Update on psychological functioning in adults with congenital heart disease: a systematic review. (June 2013) - Callus, Edward; Quadri, Emilia; Ricci, Cristian; Passerini, Cristiana; Tovo, Anna; Pelissero, Gabriele; Chessa, Massimo
The population of adults with congenital heart disease is increasing due to advancements in cardiology and cardiac surgery. Many patients face medical complications and psychosocial difficulties; however, it is not yet clear whether there is a direct relationship between medical status and the psychological functioning of these patients. This systematic review of the relevant literature is an attempt to: provide a comparison between the population of adults with congenital heart disease, the healthy reference population and similar cardiac populations when it comes to psychological functioning; explore the relationship between medical status/cardiac condition and psychological functioning; and identify the predictors of psychological distress in this population.